2022
DOI: 10.1111/ajsp.12527
|View full text |Cite
|
Sign up to set email alerts
|

The influence of fear of isolation on contact experience disclosure: Evidence from safety management of the COVID‐19 pandemic

Abstract: As the coronavirus disease 2019 (COVID‐19) pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), continues to rage, disclosure of exposure to the virus is of great significance to safety management, especially considering the long latency of the disease. We conducted a survey based on terror management theory of 2,542 people in 71 cities, representing all provinces in mainland China. The results revealed that fear of being isolated influenced disclosure of exposure to the virus and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…Previous researches have demonstrated that the impression management motivation could serve as a mediating factor between leadership behaviour and the voice behaviour [ 19 , 20 ]. Nurses feel psychologically less secure and threatened when nurse managers engage in abusive behaviours such as angry tantrums, public criticisms, and inappropriately assigned blame against nurses [ 21 , 42 ]. Individuals who feel threatened could be motivated to avoid damage to their personal image, hence, nurses may choose to withhold voice about patient safety at this point to avoid further abusive supervision by their leaders [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous researches have demonstrated that the impression management motivation could serve as a mediating factor between leadership behaviour and the voice behaviour [ 19 , 20 ]. Nurses feel psychologically less secure and threatened when nurse managers engage in abusive behaviours such as angry tantrums, public criticisms, and inappropriately assigned blame against nurses [ 21 , 42 ]. Individuals who feel threatened could be motivated to avoid damage to their personal image, hence, nurses may choose to withhold voice about patient safety at this point to avoid further abusive supervision by their leaders [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the individual leader level, abusive supervision influences impression management motivation. In addition, the organisational climate could also influence impression management motivation [ 21 ]. This implies that in a supportive speak up-related climate, nurses are more likely to exhibit impression management motivation and adopt impression management strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The public stayed at home, controlling the spread of the epidemic and protecting public health ( Chen et al, 2021 ; Wang, 2022 ). On the other hand, isolation measures hindered communication and interaction, resulting in alienation and loneliness ( Ganesan et al, 2021 ; Lu et al, 2022 ). According to Erikson's psycho-social development theory, 14–18-year-olds are adolescents who experience conflict between self-identity and role disorder; 18–25-year-olds are young adults who experience conflict between intimacy and loneliness ( Munley, 1975 ).…”
Section: Methodsmentioning
confidence: 99%